Bacterial Lipopolysaccharides Suppress Erythroblastic Islands and Erythropoiesis in the Bone Marrow in an Extrinsic and G- CSF-, IL-1-, and TNF-Independent Manner - Bisht, Kavita; Tay, Joshua; Wellburn, Rebecca N.; McGirr, Crystal; Fleming, Whitney; Nowlan, Bianca; Barbier, Valerie; Winkler, Ingrid G.; Levesque, Jean-Pierre (Frontiers in Immunology, 2020)
Anemia of inflammation (AI) is the second most prevalent anemia after iron deficiency anemia and results in persistent low blood erythrocytes and hemoglobin, fatigue, weakness and early death. AI is common in people with chronic inflammation, chronic infections or sepsis. Although several studies have reported the effect of inflammation on stress erythropoiesis and iron homeostasis, the mechanisms by which inflammation suppresses erythropoiesis in the bone marrow, where differentiation and maturation of erythroid cells from hematopoietic stem cells occurs, have not been extensively studied. Here we show that in a mouse model of acute sepsis, bacterial lipopolysaccharides (LPS) suppress medullary erythroblastic islands and erythropoiesis in a TLR-4- and MyD88-dependent manner with concomitant mobilization of hematopoietic stem cells. LPS suppressive effect on erythropoiesis is indirect as erythroid progenitors and erythroblasts do not express TLR-4 whereas erythroblastic island macrophages do. Using cytokine receptor gene knock-out mice LPS-induced mobilization of hematopoietic stem cells is G-CSF-dependent whereas LPS-induced suppression of medullary erythropoiesis does not require G-CSF-, IL-1- or TNF-mediated signaling. Therefore suppression of medullary erythropoiesis and mobilization of hematopoietic stem cells in response to LPS are mechanistically distinct. Our findings also suggest that erythroblastic island macrophages in the bone marrow may sense innate immune stimuli in response to acute inflammation or infections to rapidly convert to a pro-inflammatory function at the expense of their erythropoietic function.